Scale to measure student perception in collaborative online international learning experiences: design and validation - Rozo-García, Hugo; Alcantar-Nieblas, Carolina; Ramírez-Montoya, María Soledad (Frontiers in Education, 2024)
Introduction: Digital education is favorably positioned as a learning option; it employs various strategies, pedagogies, and methodologies, including collaborative online international learning experiences (COIL). This alternative, inherent to the digital era, transcends traditional educational methods by boosting technology to enhance learning experiences. Its given purpose is to improve learning gains, foster interculturality, internationalizing the curriculum, and strengthening skills necessary for the 21st century. Moreover, it can potentially address global educational needs that have not been fulfilled in the past.Methods: This study conducted a content validation of a scale (instrument) intending to measure students' perception of collaborative online international learning experiences (COIL) in three dimensions: a) interaction among students in digital environments, b) collaborative work in multicultural teams to achieve goals, and c) peer reflection on differences and similarities during collaboration. The study employed the Delphi method of expert judgment.Results: In the overall scale, Aiken's V values indicated that the clarity criterion did not attain an acceptable score. Therefore, a review is desired to determine which instrument items need reformulation. However, Aiken's V scores met acceptable coherence, relevance, and sufficiency values.The proposed scale contributes to research on collaborative online international learning experiences, serving as a valuable tool for future investigations, particularly those focused on measurement, and as a reference for evaluating COIL experiences among students.